Talking Back to Dominant Narratives in a High School’s Daily Morning Announcements - Edber, Hannah (Radical Teacher, 2025)
In this piece, I describe a critical analysis of the content, language, and tone of my former school site's daily morning announcements to examine how dominant narratives about the "who" and "what" of schooling are upheld and/or challenged. I then focus my discussion on an ongoing project I undertook alongside my high school students to "write back" to the school's priorities by composing and sharing their own announcements with the school community. I examine my students' announcements for their use of community cultural wealth (Yosso, 2005) and discuss the possibilities of engaging with student-generated announcements on a wider scale at the school to shed light on student identities and experiences that are too often missed in discourse in and about the school.